PEMANFAATAN MICROSOFT EXCELL DALAM PENGELOLAAN PPH 21 KARYAWAN - Rachmawati, Susan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
Small medium enterprises (UKM) is the people's business is currently being highly developed. Almost most of the UKM have had employees in the running of his business so that UKM owners was supposed to pay income tax on the income of 21 employees have been paid. To minimize time and accuracy in the calculation of the PPh 21 then owners of UKM can take advantage of Microsoft Excell available on almost computers. Research methods used in this writing is descriptive quantitative methods. Whereas the results obtained is by using Microsoft Excell can help the owners of UKM in calculating income tax payable 21 more quickly and accurately than calculating manually.Keywords: Microsoft Excell, PPH 21, UKM